THE CHANGES IN THE POSITION OF POLAND ON ITS INVESTMENT DEVELOPMENT PATH: THE RESULTS OF THE EMPIRICAL ANALYSIS - Majewska, Maria; Buszkowska-Khemissi, Eliza (Uniwersytet w Białymstoku, 2014)
The aim of this paper was to indicate on which stage of an economic development path is probably Poland. The subject of this paper was one of the economic development paths, named usually the investment development path, which model has been shaped mainly by J. H. Dunning and R. Narula. This model is also similar to the model of the economic development path proposed by M. Porter. Therefore, were discussed the changes in the main elements of this model, which took place in the Polish economy in 1995-2012. Those elements were the trade structure diveded by the degree of technological sophistication, direct investment and indicators of economic performance. In order to verify if in the case of Poland have been occurred economic dependences assumed by the representatives of this model also was carried out correlation and regression analysis. The results of the study suggest that Poland shifted to the third stage of analyzed economic development path where more emphasis is placed on innovations as the country moves toward producing more technology intensive products.
Keywords: ececonomic development path; Poland